Pengaruh Variasi Penambahan Zeolit Pada Briket Arang Jerami Padi dan Sekam Padi Terhadap Nilai Kalor dan Densitas - Ramadhan, Mohammad Mualana; Bahri, Mokh. Hairul; PN, Ardhi Fathonisyam (Indonesian Journal Publisher, 2023)
The demand for fossil energy sources continues to increase, which causes scarcity of these resources because they cannot be renewed. In Indonesia, waste rice straw and rice husks are abundant and have potential as a renewable energy source if converted into charcoal briquettes. However, currently the charcoal briquettes produced have not reached the desired level of efficiency to replace fossil fuels. Therefore, research was carried out to develop biomass energy by mixing zeolite in charcoal briquettes. This research aims to develop charcoal briquettes as an energy source from biomass. In this study, the calorific value of charcoal briquettes from rice straw with a 25% zeolite mixture had the lowest calorific value, namely 3941.2 cal/gram, while charcoal briquettes from rice straw without a zeolite mixture had the highest calorific value, namely 4581.8 cal/gram . The same thing happened to charcoal briquettes from rice husks, with the highest calorific value in charcoal briquettes without a zeolite mixture of 5390.5 cal/gram, and the lowest calorific value in charcoal briquettes mixed with 25% zeolite of 4469.1 cal/gram. The density of rice straw charcoal briquettes with a 25% zeolite mixture has the highest density value, namely 0.338 g/cm3, while rice straw charcoal briquettes without a zeolite mixture have the lowest density, namely 0.199 g/cm3. Likewise, charcoal briquettes from rice husks have the highest density in a 25% zeolite mixture with a value of 0.545 g/cm3, and the lowest density in charcoal briquettes without a zeolite mixture is 0.284 g/cm3.